The Influence of Work Motivation on Employee Performance with Job Satisfaction as an Intervening Variable - Hafsah Hafsah; Akhmad Akhmad; Andi Mapatompo (Borong Newinera Publisher, 2026)
This study aims to examine the effect of work motivation on employee job satisfaction at the Gowa Regency Trade and Industry Office. Human resources are the main factor in determining the success of an organization, so work motivation is an important aspect to improve employee performance. This study uses a quantitative approach with data collection techniques through questionnaires to the entire population of 36 people, consisting of 29 Civil Servants and 7 honorary workers. The analysis technique used is path analysis with the help of the SPSS 23 program. The results show that work motivation has a positive and significant effect on employee job satisfaction with a p-value of 0.000 < 0.05. The highest indicator of work motivation is work performance, followed by work facilities, recognition from superiors, remuneration, and working conditions. This finding strengthens the results of previous studies that state that work motivation can increase employee job satisfaction. Facts in the field show that there are efforts to provide motivation by leaders through challenging tasks, direction, and appreciation for employee performance. Thus, the higher the work motivation given to employees, the higher their level of job satisfaction. These results form an important basis for efforts to improve the quality of human resources in government environments.